2005
DOI: 10.1007/s00535-005-1692-y
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential intramural esophageal dissection successfully treated by endoscopic procedure and metal stent insertion

Abstract: Spontaneous intramural esophageal dissection is a rare disorder characterized by a lengthy laceration between the mucosal and submucosal layers of the esophageal wall, without perforation. The majority of previously reported cases of spontaneous intramural esophageal dissection were partial, and the circumferential type of intramural esophageal dissection has not been reported previously. Most spontaneous intramural esophageal dissection responds to conservative management, and usually it dose not lapse into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 16 publications
(41 reference statements)
0
37
0
Order By: Relevance
“…Esophageal perforation is described as a complication [4] and one case was treated with subtotal esophagectomy [6] . Although a spontaneous circumferential mucosal dissection was already described [7] , we are not aware of any other cases associated with eosinophilic esophagitis.…”
Section: Discussionmentioning
confidence: 79%
“…Esophageal perforation is described as a complication [4] and one case was treated with subtotal esophagectomy [6] . Although a spontaneous circumferential mucosal dissection was already described [7] , we are not aware of any other cases associated with eosinophilic esophagitis.…”
Section: Discussionmentioning
confidence: 79%
“…1) In the scenario of a circumferential dissection, a variant, which is less amenable to conservative treatment alone, the placement of an expandable metal stent has been described. 15) Upon further review of the literature, we identified two recent reports linking eosinophilic esophagitis to esophageal dissections. 9,14) In both reports, the dissection was circumferential and associated with complications: perforation in one report and abscess formation in the other.…”
Section: Discussionmentioning
confidence: 99%
“…in a bleeding diathesis), rupturing into the lumen and creating a false passage; or (ii) extrinsic, with foreign body related mucosal trauma causing an expanding sub-mucosal haematoma, and false lumen creation originating at the point of trauma. 2,3 There are also instances of the divisive force being the accidental iatrogenic insertion of a foreign body between the layers, with false passage formation along the line of insertion. 4 In cases of spontaneous intramural dissection, the patient typically presents with retrosternal pain and haematemesis.…”
Section: Oesophageal Intramural Dissectionmentioning
confidence: 99%
“…5 There are recent instances of novel endoscopic techniques being used to relieve complex cases, with stents being employed in extensive circumferential dissections, and endoscopic needle-knife incision relieving complete obstruction secondary to total membranous occlusion of the lumen. 3,4 Surgical intervention has almost no role, however.…”
Section: Oesophageal Intramural Dissectionmentioning
confidence: 99%